Effects of bank capital requirements on lending by banks and non-bank financial institutions - Peter Bednarek; Olga Briukhova; Steven Ongena; Natalja von Westernhagen (Deutsche Bundesbank, 2023)
What is the impact of a sudden and sizeable increase in bank capital requirements on the lending activity by directly affected banks and by non-affected non-bank financial institutions (NBFIs)? To answer this question, we apply a difference-in-differences methodology around the capital exercise by the European Banking Authority (EBA) in 2011 with German credit register data. We find that insurance companies, financial enterprises, and factoring companies - but not leasing companies - and Non-EBA banks expand their corporate lending relative to EBA banks. In particular, NBFIs use the opportunity to expand their credit activities, in riskier and more competitive borrower segments, but NBFIs do not seem to rely on increased bank funding to finance this expansion.
Keywords: E50; G21; G23; G28; C33; 330; non-bank financial intermediation; bank capital requirements; EBA capital exercise